Deconstructing psychosis and misperception symptoms in Parkinson's disease. Issue 9 (9th June 2017) - Nishio, Yoshiyuki; Yokoi, Kayoko; Uchiyama, Makoto; Mamiya, Yasuyuki; Watanabe, Hiroyuki; Gang, Miyeong; Baba, Toru; Takeda, Atsushi; Hirayama, Kazumi; Mori, Etsuro
Abstract : Objective: Patients with Lewy body disease develop a variety of psychotic and misperception symptoms, including visual hallucinations and delusions, as well as 'minor hallucinations', that is, a sense of presence, passage hallucinations and visual illusions. Although these symptoms have been suggested to have common underlying mechanisms, the commonalities and differences among them have not been systematically investigated at the neural level. Methods: Sixty-seven patients with Parkinson's disease underwent neuropsychological and behavioural assessments, volumetric MRI and 18F-fluorodeoxyglucose-positron emission tomography (FDG-PET). A factor analysis was performed to discover correlations among psychotic and misperception symptoms, other behavioural symptoms and neuropsychological performances. Partial least-squares correlation analysis was used to investigate the relationship between these symptoms and the joint features of MRI and FDG-PET. Results: A sense of presence, passage hallucinations and visual illusions constituted a single behavioural factor (minor hallucinations/illusions). Visual hallucinations formed another behavioural factor along with delusions, depression and fluctuating cognition (psychosis/dysphoria). Three distinct brain–behaviour correlation patterns were identified: (1) posterior cortical atrophy/hypometabolism associated with minor hallucinations/illusions and visuospatial impairment; (2) upper brainstem and thalamic atrophy/hypometabolism associated with psychosis/dysphoria and (3) frontal cortical atrophy/hypometabolism associated with non-visual cognition. No significant differences in neuroimaging findings were identified between patients who had minor hallucinations/illusions alone and patients who also had visual hallucinations. Conclusions: Our findings suggest that combined damage to the upper brainstem/thalamus and the posterior neocortex underlies both minor hallucinations/illusions and visual hallucinations and that the former pathology is more associated with visual hallucinations/frank psychosis and the latter is more associated with minor hallucinations/illusions.